(untitled) (Research, Society and Development, 2020)
The objective of this article is to investigate how certain public policies in the scope of Education at a higher level are impacting on access to it, notably with regard to the composition of gender and race, in parallel to the regions in Brazil. Within this set of policies, we studied the databases made available by the Federal Government on the University for All Program - PROUNI from 2005 to 2016, with regard to the occupation of scholarships. We combine this empirical dimension with the theoretical proposal of Gerth and Mills, in which six guiding questions must be answered for any analysis of social change. We observed that the PROUNI policy between 2005 and 2016 expanded access to higher education in the perspective of social change in relation to the groups that access it. On the one hand, we see that there is a prevalence of women over men in accessing scholarships at private universities. On the other hand, when we look only at the grants awarded to women, we see a backlog of inequality that still remains. When we see the composition of race, we perceive the inequality in an even stronger character, especially when we have in mind the southeast and south regions. White women predominate in practically all Brazilian regions, in a historical process in which this process has been reducing, although in certain regions such discrepancy is accentuated.